The effect of different gonad shields on entrance surface dose to the ovary for PA chest radiography - Mohd Ali Hanafiah, Muhd Ilhami; Moey, Soo Foon; Che Mohamed, Norfariha (Kuliyyah of Allied Health Sciences, International Islamic University Malaysia, 2021)
Background: The use of higher tube potential (kVp) and lower tube current-time (mAs) can deliver a lower patient exposure dose in chest radiography. However, the production of scattered radiation especially with high kVp technique can cause an increase in radiation dose to the area outside the collimated region if it is not optimized. The study aimed to compare the effect of different tube potentials on the entrance surface dose (ESD) of the ovary without gonad shield, with shadow shield and with contact shield using Optically Stimulated Luminescence Dosimeter (OSLD) during PA chest radiography. This study also sought to determine the ESD differences when using the shadow and contact gonad shield when exposed with different kVp. Materials and Methods: The experimental study was performed in the Radiography Laboratory, International Islamic University Malaysia, Kuantan. The ESD of the ovary was measured using OSLD placed at the back of the PBU-50 phantom at the level of the ovary. Tube potentials ranging from 109 kVp to 150 kVp were utilized. Result: The ESD to the ovary decreased with increased tube potential. Although there was no significant difference in ESD to the ovary without gonadal shielding and with shielding, the ESD was the highest at the lowest kVp used without shielding. The contact gonad shield resulted in a lower ESD than the shadow gonad shield even though statistically it was not significant. Conclusion: Use of high kVp and contact gonad shield for PA chest can maximize the radiation protection for the patient